2017
DOI: 10.31233/osf.io/yab83
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How has our knowledge of dinosaur diversity through geologic time changed through research history?

Abstract: Assessments of dinosaur macroevolution at any given time can be biased by the historical publication record. Recent studies have analysed patterns in dinosaur diversity that are based on secular variations in the numbers of published taxa. Many of these have employed a range of approaches that account for changes in the shape of the taxonomic abundance curve, which are largely dependent on databases compiled from the primary published literature. However, how these 'corrected' diversity patterns are influenced… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 80 publications
(192 reference statements)
1
24
0
Order By: Relevance
“…The high abundance of theropod remains from northern mid‐latitudes and the relative scarcity of specimens at other latitudes strongly suggests a historical focus on Europe, North America, northern Africa and East Asia, and the comparative neglect of South America, southern Africa and Australia (Benton ; Tennant et al . ). This is supported by the significantly higher completeness distributions of theropods from Asia and North America (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The high abundance of theropod remains from northern mid‐latitudes and the relative scarcity of specimens at other latitudes strongly suggests a historical focus on Europe, North America, northern Africa and East Asia, and the comparative neglect of South America, southern Africa and Australia (Benton ; Tennant et al . ). This is supported by the significantly higher completeness distributions of theropods from Asia and North America (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Benton () similarly found that recent dinosaur species described from European deposits were of the poorest quality in comparison to other continents, and attributed this to historical research efforts and an overfamiliarity with deposits, corroborated by high European theropod Good's u sampling coverage estimated by Tennant et al . (). This, however, cannot be solely driven by human sampling effort, but is more likely to reflect the lack of consistent availability of terrestrial Mesozoic horizons yielding fossiliferous material.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A key assumption of any richness estimator is that sampling is unbiased. However, palaeontological research probably exhibits a ‘novelty bias’—a tendency to prioritise publication of new taxa over new occurrences of named taxa (Alroy, ; Tennant et al., ). At least in the early phases of discovery, this bias results in inflated counts of singletons, which bias estimates of sample coverage downwards, and estimated richness upwards.…”
Section: Discussionmentioning
confidence: 99%
“…These data are exceptionally complete and well‐vetted in the PaleoDB, and there has been intense interest in reconstructing dinosaur diversity patterns (e.g. Barrett, McGowan, & Page, ; Butler, Benson, Carrano, Mannion, & Upchurch, ; Starrfelt & Liow, ; Tennant, Chiarenza, & Baron, ; Upchurch, Mannion, Benson, Butler, & Carrano, ), including in the initial publication of TRiPS. Global diversity curves suffer from profound issues with highly‐variable sampling universes (Appendix ), and here we only analyse dinosaur data at global level to enable direct comparison with Starrfelt and Liow ().…”
Section: Methodsmentioning
confidence: 99%